Hand Gesture Recognition for Human Computer Interaction through KNN Algorithm and Mediapipe - Sai Rohit, Shaik; Kandoi, Raunak; Kumar, Sandeep (International Journal of Computer Sciences and Engineering, 2023)
In our day to day life humans interact with computers or machines very frequently and these interactions result in completion of meaningful tasks or scheduled jobs. These interactions can involve a lot of applications like gaming, typing, scrolling, pointing, remote arm movement, etc. Out of all the ways of interacting such as mechanical movement. The most effective one is thought to be through hand because the mechanical ones even include the movement of hand ultimately, so in order to make this interaction more convenient and efficient there was an idea of developing hand gesture recognition and it was later implemented but often it involved special instruments such as gloves with sensors or particular background. This proposed paper emphasizes the more effective way of human computer interaction which is hand gesture recognition. There are three main modules which are hand detection and hand tracking and hand gesture recognition. There are several applications of this way of interaction the user can customize to their own use. This model is fast and accurate and it can go up to 30fps and the main applications include the video game stimulation, virtual board and many other useful human computer interactions. The proposed model can detect hand even in strained backgrounds and without gloves in almost all of the cases and the model is robust and smooth. The hand gestures are one of the most natural ways of communication in humans rather than input through keyboards and mouse. This model can be used in VR and AR stimulations which would need a better way of human computer interaction than a keyboard and mouse. The main objective of this paper is to employ a new model to improve the human computer interaction. In the proposed model a menu will be displayed with the numbers representing the action desired by the user let us say 1. Represents the virtual mouse 2. Represents the virtual keyboard 3. Represents the other menu where a series of actions can be defined by the user.